Legislative Regulation of Criminal Liability for Environmental Crimes - Buribayev, Yermek A.; Khamzina, Zhanna A.; Suteeva, Canzada; Apakhayev, Nurlan Zh.; Kussainov, Sergazy Zh.; Baitekova, Kantkul Zh. (Journal of Environmental Accounting and Management, 2026)
The only effective mechanism in the fight against global changes and processes is a conscious attitude to the problem of the planet's population. The purpose of the study was to compare the national and international experience in combating environmental crime and offenses, to identify advantages and disadvantages, and to develop proposals for possible improvement of existing legislation and practical tools in the matter of environmental offenses in the field of nature conservation. As a result, the system of ensuring and compliance with the criminal environmental legislation of the Republic of Kazakhstan, its weaknesses and strengths, advantages and disadvantages were considered.